GAMBARAN ASUPAN SERAT, NATRIUM DAN TEKANAN DARAH PADA PENDERITA STROKE HEMORAGIK DI RUANG RAWAT JALAN RSUD PROF. DR. W. Z. JOHANNES KUPANG - Riantoby, Eulentriana Suban Raya; Boro, Regina Maria (Kupang Journal of Food and Nutrition Research, 2025)
Stroke disease became the second highest cause of death in the world in 2015 and the highest cause of death in Indonesia in 2014. The prevalence of stroke in people over 15 years of age in Indonesia based on the results of the 2018 Village Health Research (Riskesdas) was 10.9/mil, which means that out of 1000 residents, 10.9 residents experienced stroke, the province with the most residents experiencing stroke was East Kalimantan province with a total of 14.7/mil, while South Kalimantan province was ranked 6th with the number of stroke sufferers reaching 13.3/mil. Research Objectives: To identify fiber, sodium and blood pressure intake in hemorrhagic stroke patients at Prof. Dr. W. Z. Johannes Kupang Regional Hospital. Research Methods : The type of research used was an observational study with a cross-sectional design. This descriptive study was based on the research objectives, namely to determine the description of fiber, sodium and blood pressure intake in hemorrhagic stroke patients in outpatient care at Prof. Dr. W. Z. Johannes Kupang Regional Hospital. Dr. W. Z Johannes Kupang. Results : The results of the univariate study showed that the gender of hemorrhagic stroke patients was mostly female, 17 people (56.7%). The highest education was high school, 16 people (53.3%). The level of fiber intake of hemorrhagic stroke patients was in the severe deficit category, 12 people (40.0%). The level of sodium intake of hemorrhagic stroke patients was in the severe deficit category, 30 people (100%).